Um Ensaio Sobre História Oral e Educação Matemática: pontuando princípios e procedimentos - Gaertner, Rosinete; Baraldi, Ivete Maria [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2008)
Recently, we can perceive an intensification of assignments developed into Mathematical Education with the use of oral history as a research methodology. In this article, facing the living experiences during the preparation of our Phd tasks and later, when we had the role of advisors of scientific papers and of Postgraduate students in their researches also using the same methodology, we discussed the implication of ethics, mathematical education and oral history. Furthermore, we enunciated possibilities of the posture of the researcher before interviews, texts and iconography - photos and several images-provided by collaborators of our projects on Oral history and Mathematical Education.
An Essay About Oral History and Mathematical Education: setting principles and procedures
Keywords: Oral history; Mathematical Education